The Opportunities and Challenges Analysis of the Coffee Shop Business during the Covid Pandemic 19 in Pekanbaru - Kiki Joesyiana; Asepma Hygi Prihastuti; Desi Susanti (Jurnal Pendidikan Ekonomi (JUPE), 2022)
Currently, the coffee shop is one of the growing trends in the coffee businesses that are of great interest, not only in Pekanbaru but throughout Indonesia, the existence of a coffee shop business is increasing growth. However, in early 2020, the world faced Covid 19 pandemic that is greatly impacting the life aspects including the coffee shop business. This research aims to know the opportunities and challenges as the reference for the owner to run the business ahead in Covid 29 Pandemic and to be more creative to take advantage of its opportunities and challenges to keep the business survived and to make a profit. The Descriptive qualitative analysis was employed in this research with a SWOT framework. Primary and secondary data were used in this research, it was obtained from observation and in-depth interview related to opportunities and challenges of coffee shop business in Covid 19 Pandemic and also the distribution of the questionnaire. SWOT analysis and SWOT matrix show that the Coffee Shop business in Pekanbaru is in cell 1 (Grow and Build). Intensive strategy (market penetration, product development, and market development) was the most appropriate strategy to be implemented in this cell part of the Coffee Shop business in Pekanbaru